1997
DOI: 10.1002/(sici)1097-0215(19971219)74:6<565::aid-ijc1>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Potential role ofbcl-2 as a suppressor of tumour angiogenesis in non-small-cell lung cancer

Abstract: It has been reported that genes regulating apoptosis may play a role in tumoral angiogenesis. This study examined the relationship between tumour vascularization, a measure of tumour angiogenesis, and bcl‐2 and p53 expression in operable non‐small‐cell lung cancer (NSCLC). The relationship between bcl‐2, p53 and tumour vascularization and epidermal‐growth‐factor‐receptor(EGFR) and c‐erbB‐2 expression was also studied. Tissue sections from resected tumour specimens of 107 NSCLC patients were evaluated immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 28 publications
4
24
0
Order By: Relevance
“…HIF2α was higher in cases with high or low MVD but was significantly lower in cases with a medium degree of vascularization. This U-like-shaped association of HIF2α with MVD is in accordance with previous studies of ours where not all VEGF-, TP-or bFGF-expressing tumours show an increase in angiogenesis (Koukourakis et al, 1997b(Koukourakis et al, , 2000Giatromanolaki et al, 1998Giatromanolaki et al, , 2000. We suggest that although hypoxia triggers the expression of a cascade of angiogenic factors through HIF stabilization, the process of angiogenesis is subject to other modulators.…”
Section: Hif1α/2α Expression In Nsclc 887supporting
confidence: 91%
“…HIF2α was higher in cases with high or low MVD but was significantly lower in cases with a medium degree of vascularization. This U-like-shaped association of HIF2α with MVD is in accordance with previous studies of ours where not all VEGF-, TP-or bFGF-expressing tumours show an increase in angiogenesis (Koukourakis et al, 1997b(Koukourakis et al, , 2000Giatromanolaki et al, 1998Giatromanolaki et al, , 2000. We suggest that although hypoxia triggers the expression of a cascade of angiogenic factors through HIF stabilization, the process of angiogenesis is subject to other modulators.…”
Section: Hif1α/2α Expression In Nsclc 887supporting
confidence: 91%
“…This speculation may explain the responsiveness of tumors with high Bcl-2 expression to chemotherapy or RT. Finally, several studies showed that high expression of Bcl-2 is associated with low tumor vascularization in NSCLC probably by suppression of angiogenic factor such as vascular endothelial growth factor, suggesting the correlation with better outcome [43][44][45][46]. However, further studies are essential to prove these suppositions.…”
Section: Discussionmentioning
confidence: 99%
“…Ten were excluded (Giatromanolaki et al, 1996a(Giatromanolaki et al, ,b, 1997Koukourakis et al, 1997Koukourakis et al, , 1999Koukourakis et al, , 2000aKakolyris et al, 1999) because identical cohorts of patients were used in other selected publications. In the eight remaining eligible studies (Apolinario et al, 1997;Kawaguchi et al, 1997;Pastorino et al, 1997;Duarte et al, 1998;Ohta et al, 1999;O'Byrne et al, 2000;Han et al, 2001;Hasegawa et al, 2001), published between 1996 and 2001, the total …”
Section: Studies Selection and Characteristicsmentioning
confidence: 99%